Pengaruh Sertifikat Halal Terhadap Pendapatan UMKM Produk Kuliner di Musi Rawas Utara - Arsyad, Syafira Rizki; Azhar, Jeihan Ali (CV. ULIL ALBAB CORP, 2025)
This study was conducted with the aim of analyzing the effect of halal certification on products on increasing the income of business actors. This research is included in quantitative research with a questionnaire method to obtain the data. The analysis technique performed is to utilize the SPSS application through the multiple linear regression method. The sampling of this study were business actors in North Musi Rawas as many as 43 business actors so that the samples taken using saturated samples of all business actors were taken as responses.The provision of halal certification for culinary and food products in North Musi Rawas Regency has a significant and positive impact on increasing sales from MSME players. The effect of halal certification on income levels is 16.1% affecting the level of community income. For this reason, MSMEs will experience an increase in sales if they are encouraged by the ownership of halal certification for each product.